If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(0) + -3y = 6 Multiply 5 * 0 0 + -3y = 6 Anything times zero is zero. 0 + -3y = 6 Remove the zero: -3y = 6 Solving -3y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-3'. y = -2 Simplifying y = -2
| -r+2r=4 | | 2logx=x-2 | | 0=x+4x | | 3(2x-1)=12x+10 | | 13=6x+3-2 | | 3.2=x+1.3 | | 14=4b-5+3 | | 2x*3=3x-4/3 | | 7(x+4)=-4 | | 1+2p+p=-8 | | -9(2p+4)=3(-6p-12) | | 2x^4+18=20x^2 | | 8/9x6 | | Abx=c | | -2/e=3 | | 72*7= | | Bc=ac | | 16h=(2h-10) | | 2x+5y+1x+3y=1445 | | -7265+185t=-12790 | | 1/2×(2x-6)=14 | | 4w+12=44 | | 14x/-28y-1 | | 6x+16=15x-38 | | 10n-27-3n=190 | | -5(0.2x+1.4)=27 | | .003x+.01=.0005x-.008 | | n-12=-8 | | 5xy=12 | | 5a-4a-3=21 | | 4y+17=81 | | 20x^3-89x^2+37x-4=0 |